The Prevalence of Antibiotic Resistance Genes and Toxin Producing Genes in Methicillin Resistant Staphylococcus aureus Isolates from Diabetic Foot Ulcer - Surekha K. Chavan, Geeta Karande, Kailas Datkhile (South Eastern European Journal of Public Health, 2025)
Antibiotic resistance in bacterial pathogens coupled with toxin production can have severe impact on health. Diabetic foot ulcer (DFU) is an extreme pathophysiological condition difficult to treat due to bacterial infections. The present study investigates the antibiotic resistance, prevalence of antibiotic resistance genes and virulence genes in one of the most common Gram-positive pathogen Methicillin resistant Staphylococcus aureus from DFUs of Indian patients. The samples were collected form DFU using sterile swab, needle aspiration and curetting. A total of 150 Methicillin resistant Staphylococcus aureus isolates were tested for antibiotic resistance using various drugs. The prevalence of the genes involved in antibiotic resistance (MecA) and toxin production (FemA, coa, nuc, aroA, alpha-toxin, exfA, FabA, FabB, and pvl) was studies using PCR analysis. Among 150 Methicillin resistant Staphylococcus aureus isolates 100% isolates were resistant to Benzylpenicillin and Cefoxitin.Most of the isolates were sensitive to Linezolid (4%; 6 isolates), Tigecycline (4%; 6 isolates), Teicoplanin (5.33%; 8 isolates), Nitrofutantion (6%; 9 isolates), and Vancomycin (8%; 12 isolates). Mec 1 gene was present in 84 (54%) isolates. MecA gene was present in81(54%) isolates. Among toxin producing genes Fab-A105(70%) was the most prevalent gene. MecA gene was present in 100% isolates resistant to Benzylpenicillin, Cefoxitin, and Levofloxacin. These results suggest that antibiotic resistance pattern of MRSA isolates vary for different drugs. The possibility of the presence of other antibiotic resistance genes and toxin producing genes in Methicillin resistant Staphylococcus aureus isolates could not be denied.